(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the syntactic-semantic interface of the temporal category across different languages. By analyzing syntactic structures and their corresponding semantic interpretations, the study aims to unveil the complexities of temporal encoding. Employing a cross-linguistic methodology, the research compares tense and aspect representation in English, highlighting key syntactic and semantic differences. The findings contribute to a deeper understanding of how languages structure temporal meaning.